One size fits all? Challenges faced by physicians during shift handovers in a hospital with high sender/recipient ratio - Yang, Xi Jessie (2015)
INTRODUCTION: The aim of the present study was to investigate the challenges faced by physicians during shift handovers in a university hospital that has a high handover sender/recipient ratio. METHODS: We adopted a multifaceted approach, comprising recording and analysis of handover information, rating of handover quality, and shadowing of handover recipients. Data was collected at the general medical ward of a university hospital in Singapore for a period of three months. Handover information transfer (i.e. senders’ and recipients’ verbal communication, and recipients’ handwritten notes) and handover environmental factors were analysed. The relationship between ‘to-do’ tasks and information transfer, handover quality and handover duration was examined using analysis of variance. RESULTS: Verbal handovers for 152 patients were observed. Handwritten notes on 102 (67.1%) patients and handover quality ratings for 98 (64.5%) patients were collected. Although there was good task prioritisation (information transfer: p < 0.005, handover duration: p < 0.01), incomplete information transfer and poor implementation of non-modifiable identifiers were observed. The high sender/recipient ratio of the hospital made face-to-face and/or bedside handover difficult to implement. Although the current handover method (i.e. use of telephone communication) allowed for interactive communication, it resulted in systemic information loss due to the lack of written information. The handover environment was chaotic in the high sender/recipient ratio setting, and the physicians had no designated handover time or location. CONCLUSION: Handovers in high sender/recipient ratio settings are challenging. Efforts should be made to improve the handover processes in such situations, so that patient care is not compromised.